Adverse intrapartum outcome in pregnancies complicated by small for gestational age and late fetal growth restriction undergoing induction of labor with Dinoprostone, Misoprostol or mechanical methods: A systematic review and meta-analysis. (September 2020) - Familiari, Alessandra; Khalil, Asma; Rizzo, Giuseppe; Odibo, Anthony; Vergani, Patrizia; Buca, Danilo; Hidaka, Nobuhiro; Di Mascio, Daniele; Nwabuobi, Chinedu; Simeone, Serena; Mecacci, Federico; Visentin, Silvia; et al.
Abstract: Objective: To investigate the outcome of pregnancies with small baby, including both small for gestational age (SGA) and late fetal growth restriction (FGR) fetuses, undergoing induction of labor (IOL) with Dinoprostone, Misoprostol or mechanical methods. Study design: Medline, Embase and Cochrane databases were searched. Inclusion criteria were non-anomalous singleton pregnancies complicated by the presence of a small fetus, defined as a fetus with estimated fetal weight (EFW) or abdominal circumference (AC) <10th centile undergoing IOL from 34 weeks of gestation with vaginal Dinoprostone, vaginal misoprostol, or mechanical methods (including either Foley or Cook balloon catheters). The primary outcome was a composite measure of adverse intrapartum outcome. Secondary outcomes were the individual components of the primary outcome, perinatal mortality and morbidity. All the explored outcomes were reported in three different sub-groups of pregnancies complicated by a small fetus including: all small fetuses (defined as those with an EFW and/or AC <10th centile irrespective of fetal Doppler status), late FGR fetuses (defined as those with EFW and/or AC <3rd centile or AC/EFW <10th centile associated with abnormal cerebroplacental Dopplers) and SGA fetuses (defined as those with EFW and/or AC <10th but >3rd centile with normal cerebroplacental Dopplers). Quality assessment of each included study was performed using the Risk of Bias in Non-randomized Studies-of Interventions tool (ROBINS-I), while the GRADE methodology was used to assess the quality of the body of retrieved evidence. Meta-analyses of proportions and individual data random-effect logistic regression were used to analyze the data. Results: 12 studies (1711 pregnancies) were included. In the overall population of small fetuses, composite adverse intra-partum outcome occurred in 21.2 % (95 % CI 10.0−34.9) of pregnancies induced with Dinoprostone, 18.0 % (95 % CI 6.9−32.5) of those with Misoprostol and 11.6 % (95 % CI 5.5−19.3) of those undergoing IOL with mechanical methods. Cesarean section (CS) for non-reassuring fetal status (NRFS) was required in 18.1 % (95 % CI 9.9−28.3) of pregnancies induced with Dinoprostone, 9.4 % (95 % CI 1.4−22.0) of those with Misoprostol and 8.1 % (95 % CI 5.0−11.6) of those undergoing mechanical induction. Likewise, uterine tachysystole, was recorded on CTG in 13.8 % (95 % CI 6.9−22.3) of cases induced with Dinoprostone, 7.5 % (95 % CI 2.1−15.4) of those with Misoprostol and 3.8 % (95 % CI 0–4.4) of those induced with mechanical methods. Composite adverse perinatal outcome following delivery complicated 2.9 % (95 % CI 0.5−6.7) newborns after IOL with Dinoprostone, 0.6 % (95 % CI 0–2.5) with Misoprostol and 0.7 % (95 % CI 0–7.1) with mechanical methods. In pregnancies complicated by late FGR, adverse intrapartum outcome occurred in 25.3 % (95 % CI 18.8−32.5) of women undergoing IOL with Dinoprostone, compared to 7.4 % (95 % CI 3.9−11.7) of those with mechanical methods, while CS for NRFS was performed in 23.8 % (95 % CI 17.3−30.9) and 6.2 % (95 % CI 2.8−10.5) of the cases, respectively. Finally, in SGA fetuses, composite adverse intrapartum outcome complicated 8.4 % (95 % CI 4.6−13.0) of pregnancies induced with Dinoprostone, 18.6 % (95 % CI 13.1−25.2) of those with Misoprostol and 8.7 (95 % CI 2.5−17.5) of those undergoing mechanical IOL, while CS for NRF was performed in 8.4 % (95 % CI 4.6−13.0) of women induced with Dinoprostone, 18.6 % (95 % CI 13.1−25.2) of those with Misoprostol and 8.7 % (95 % CI 2.5−17.5) of those undergoing mechanical induction. Overall, the quality of the included studies was low and was downgraded due to considerable clinical and statistical heterogeneity. Conclusions: There is limited evidence on the optimal type of IOL in pregnancies with small fetuses. Mechanical methods seem to be associated with a lower occurrence of adverse intrapartum outcomes, but a direct comparison between different techniques could not be performed.